Adolescência, risco e proteção: um estudo narrativista-dialógico sobre trajetórias de vida - Bessa, Letícia Leite (2010)
This research entitled Adolescence, risk and protective: a study on dialogic narrativist-life trajectories it is a study interested in the life stories of teens who live in situations of social vulnerability in order to understand what their narratives reveal about risk and how it handles the social construction of these meanings. For both, were interviewed using the technique of auto-biographical narrative interview, three teenagers, students of the School of Dance and Social Integration for Children and Adolescents - EDISCA, non-governmental organization that works with an educational approach centered on art together children and adolescents from socially disadvantaged areas of the city of Fortaleza. Two theoretical perspectives framed the approach taken with this problem: the narrativist and dialogic. The first supported in studies interested in the narrative nature of human experience, with the exponent of the psychologist Jerome Bruner. The second grounded in theoretical elaborations of Mikhail Bakhtin concerning the processes of dialogism, polyphony and otherness. Theoretically also contributed to the reflections of human development theory RedSig on "constraints" and "positioning" as well as the elaboration of positive psychology on risk, protection and resilience. Independent ontological status of events and circumstances that present a danger or harm to young people, this work avoids fixing the meaning of "social risk" by investigating, by means of a narrative and dialogical perspective, how teens understand the risk in their daily lives and how they can interpret such meanings in dialogue with the narrators and the scholarly literature on the topic. From the life stories of three teenagers showed that each, in their way, might reveal their meanings about risk and social protection, if possible, in some cases, an approach to the concept of resilience. In these stories, listen to signals on the paths of other young people close to them, acclimated in risky situations. In the co-construction of life narratives, families appear highlighted. The EDISCA shows up as a voice that helps build a healthy development. It is a common expectation of a happy future. The intention of this research is to contribute to the academic and social dialogues about teenager living in socially vulnerable, but also about risk and social protection, breaking stigmas about the fate of adolescents with certain conditions, understanding them as protagonists of their "life stories shared." In addition to funding considerations to institutions and professionals, especially to psychologists, to develop actions with adolescents about their subjective constructions.